UPAYA PENYELESAIAN TERHADAP WANPRESTASI DALAM LAYANAN JASA FOTOGRAFI DI KOTA PADANG - Yunanda Sukma, Jasman Nazar (INTELIGENSIA MEDIA, 2024)
This research examines the phenomenon of default in photography service agreements in Padang City and its settlement efforts. In the rapidly growing photography industry, especially for wedding documentation, there are often disagreements between vendors and clients that lead to default. Forms of default include late payment, non-conformity of results, or unilateral cancellation. This research uses a normative-empirical method with secondary data from analyzing regulations and literature, and primary data from interviews. The results show that defaults generally occur due to less robust agreements, both oral and written. Default resolution is usually done through non-litigation efforts such as notification and deliberation, while legal action is the last option. This research aims to increase understanding and provide recommendations regarding default resolution in photography services, helping legal practitioners, policy makers, and the public to achieve legal certainty and justice.